2012
DOI: 10.3109/17482968.2012.688837
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance myography as a biomarker to assess ALS progression

Abstract: Electrical impedance myography (EIM), a non-invasive, electrophysiological technique, has preliminarily shown value as an ALS biomarker. Here we perform a multicenter study to further assess EIM’s potential for tracking ALS. ALS patients were enrolled across eight sites. Each subject underwent EIM, handheld dynamometry (HHD), and the ALS Functional Rating Scale-revised (ALSFRS-R) regularly. Techniques were compared by assessing the coefficient of variation (CoV) in the rate of decline and each technique’s corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 26 publications
3
117
0
4
Order By: Relevance
“…Thus, the method is not truly electrophysiological, in the sense that it is not producing excitation of muscle fibers, but is rather electromorphological. Studies of EIM to date have shown substantial sensitivity to ALS disease status and rate of progression, and high reliability [60][61][62]. Animal work has also strongly supported this concept [63,64].…”
Section: Electrical Impedance Myographymentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, the method is not truly electrophysiological, in the sense that it is not producing excitation of muscle fibers, but is rather electromorphological. Studies of EIM to date have shown substantial sensitivity to ALS disease status and rate of progression, and high reliability [60][61][62]. Animal work has also strongly supported this concept [63,64].…”
Section: Electrical Impedance Myographymentioning
confidence: 73%
“…For example, patients in a drug study may report less progression than those not on an experimental drug simply because they believe the drug might be working. Indeed, a natural history study evaluating ALSFRS-R along with other measures actually showed the ASLFRS-R to be more sensitive to progression than had been reported in other studies [12], perhaps because there was no subjective bias toward a drug having a therapeutic effect. Another limitation of the ALSFRS-R is that it may be affected by the degree of social support and the presence of depression [13].…”
Section: Introductionmentioning
confidence: 94%
“…Electrical impedance myography (EIM) developed by a single laboratory involves a set of electrodes placed over the belly of the muscle [68,69]. A small, high-frequency electrical current is applied and the surface voltage can then be measured.…”
Section: Electrical Impedance Myographymentioning
confidence: 99%
“…Death in ALS is almost always due to respiratory failure, an aspect of loss of strength not captured in extremity measurements. Second, power analyses comparing sample sizes required to show meaningful effects in different outcome measures have suggested that the ALSFRS-R has the potential to show a statistically significant difference with fewer patients per group than other measures, including quantitative muscle strength and vital capacity [36,38]. These estimates of power are derived primarily from 2 factors: rate of change in the measure over time, and variability across patients.…”
Section: Quantitative Muscle Testingmentioning
confidence: 99%